THU0566 Certain Autoimmune Diseases are Associated with Distinctive Karyotypes and Outcome in Patients with Myelodysplastic Syndrome. (9th June 2015) - Lee, S.J.; Joo, S.H.; Lee, E.B.; Song, Y.W.; Yoon, S.-S.; Park, J.K.
Abstract : Background: Up to 10% of patients with myelodysplastic syndrome (MDS) develop features of autoimmune diseases (AD). However, the factors associated with AD and their effects on MDS outcome have not been fully elucidated Objectives: This study is aimed to investigate whether AD is associated with specific karyotype and outcome in patients with MDS. Methods: A total of 67 MDS patients with AD and 201 age-, sex matched MDS patients without AD (at 1:3 ratio), who received medical care at Seoul National University Hospital from January 2000 through July 2014, were enrolled in this study. Clinical features and outcomes of MDS patients with vs. without AD were examined. Results: The mean age (±SD) at MDS diagnosis was 54±17.1 years and 55% were female. Among MDS patients with AD, skin disease (Sweet's syndrome and panniculitis) was most prevalent with 26 (39%) of 67 observed AD cases, followed by 9 (13%) Behcet's disease, 8 (12%) vasculitis, 9 (13%) rheumatoid arthritis, 4 (6%) myositis, 3 (5%) spondyloarthropathy and 2 (3%) systemic lupus erythematous. 5q deletion was more frequent in MDS with AD as compared to those without AD (23% vs. 11%, p=0.023) and was associated with a 6.08 fold-increased risk for skin disease (95% confidence intervals (CI): 2.41-15.36, p<0.001). The trisomy 8 was significantly more frequent in Behcet's disease (OR 6.47, 95% CI: 1.4-30.6, p=0.024). Strikingly, the presence of skin disease was associated with a 3.29 fold increase in mortality (p=0.003 by Cox regression analysis). Conclusions: Certain ADs are associated with distinctive MDS karyotypes and worse outcomes. Thus, the presence of AD features should be considered for evaluation of prognosis and so the treatment intensity. Disclosure of Interest: None declared